Posture dependent ankle and foot muscle responses evoked by Achilles’ tendon vibration - Vizirgianakis, Spiridon; Amiridis, Ioannis G.; Mademli, Lida; Tsiouri, Chrisi; Hatzitaki, Vassilia (Neuroscience letters, 2021)
•Heteronymous Ia afferents link the soleus to flexor digitorum brevis (FDB) muscle.•Soleus and FDB activity increased in response to Achilles’ tendon vibration.•Soleus and FDB sustained activation after vibration in standing and leaning.•Soleus and FDB synergy is posture depedent. To investigate the link between the triceps surae and the intrinsic muscles of the foot, often underestimated in posture maintenance, we asked how Achilles’ tendon vibration modulates the EMG activity of the soleus and flexor digitorum brevis (FDB) muscles during different postural tasks: sitting, standing and forward leaning. Young healthy participants (n = 19, age = 24 ± 7.4 years) stood for 60 s in three visually controlled postures, while vibration (1.5–1.8 mm, 80 Hz) was bilaterally applied over the Achilles' tendon during the middle 20 s. Center of Pressure (CoP) and EMG activity of the soleus and FDB muscle were summarized in 5 s epochs and compared across time (before, during and after vibration) and postural tasks. Achilles’ tendon vibration shifted the CoP position forward in sitting and backward in standing and leaning and increased the root mean square of the CoP velocity to a greater extent in standing and leaning compared to sitting. Soleus and FDB EMG amplitude also increased in response to vibration. These responses were posture dependent, being greater in standing (soleus: 57 %, FDB: 67 % relative to pre-vibration) compared to sitting (soleus: 36 %, FDB: 27 % relative to pre-vibration) and leaning (soleus: 26 %, FDB: 8% relative to pre-vibration). After vibration offset, both soleus and FDB showed sustained activation across all three postures. Results highlight the presence of Ia afferent projections from the soleus to the α motor neurons of the FDB muscle triggered by Achilles’ tendon vibration. This link is posture dependent serving a functional role in standing and forward leaning in the presence of externally applied perturbations.